Determinasi Tantangan FI, Manfaat FI, dan Realisasi FI Pada Strategi Agility Diversifikasi Investasi - Yuyun Ristianawati; Setyo Budi Hartono (ITB AAS INDONESIA Surakarta, 2022)
Financial inclusion (FI) is an aspect of risk inherent in financing where this is an Islamic law that is applied in mudharabah and musyarakah contracts. Its application can be done through the derivation of RBT with portfolio theory, where from the second derivation it produces a strategic agility diversification investment (SADI) proposition. To be able to improve the financial performance of FIs in the form of challenge facing, benefits, and realization, it is necessary to determine first in the form of an agility strategy which can then be used in investment derivation to improve financial performance directly or indirectly. This research is a conceptual that combines the derivation of RBT with portovolo theory in producing a new concept in the form of SADI. The results show that FI can be used in determining SADI to generate financial performance for Islamic banks. Challenge facing of FI can function in changing aspects of financing without using collateral. Meanwhile, when these challenges can be overcome, the benefits of FI can be felt in the form of open access for those who are not lucky. And the reality is that you can use technology to make it easier to carry out financial inclusion for those who are less fortunate.